Low dielectric and electromagnetic shielding LCP composite material and preparation method thereof

By using low-dielectric glass fibers, metal-plated low-dielectric glass fibers and conductive fillers in LCP materials to blend them with LCP resin and polytetrafluoroethylene resin, a conductive network is solved, and the dielectric and electromagnetic shielding performance of LCP materials is insufficient. The problem is that low dielectric, electromagnetic shielding and thermal conductivity have been improved, and is suitable for high-speed and high-frequency signal transmission in the 5G era.

CN119264695APending Publication Date: 2025-01-07HENAN TIANHAI HEJU NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411477752.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

LCP materials have insufficient dielectric and electromagnetic shielding performance in the 5G era, making it difficult to meet the needs of high-speed and high-frequency signal transmission.

Method used

Low-dielectric glass fiber, metal-plated low-dielectric glass fiber and conductive filler are blended with LCP resin and polytetrafluoroethylene resin, and low-dielectric, electromagnetic shielded LCP composite materials are prepared through heating, melting and extrusion granulation processes, and constructed Conductive network to improve electromagnetic shielding and thermal conductivity.

Benefits of technology

It realizes composite materials with low dielectric constant, small dielectric loss, strong electromagnetic shielding ability and good thermal conductivity, and is suitable for applications in electronic components and complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264695A_ABST
    Figure CN119264695A_ABST
Patent Text Reader

Abstract

The invention provides a low dielectric and electromagnetic shielding LCP composite material and a preparation method thereof, belongs to the technical field of high polymer material processing, and aims to solve the technical problem of poor dielectric and electromagnetic shielding performance of an LCP material. The LCP composite material is prepared from the following raw materials: LCP resin, polytetrafluoroethylene resin, low-dielectric glass fibers, electroplated metal low-dielectric glass fibers, conductive filler and auxiliaries. According to the invention, the LCP resin is used as matrix resin to be compounded with the polytetrafluoroethylene resin, so that the obtained resin matrix not only has excellent mechanical properties, weather resistance, solvent resistance and the like, but also has excellent dielectric properties, and is very low in dielectric constant and dielectric loss; the low-dielectric glass fiber, the electroplated metal low-dielectric glass fiber and the conductive filler are compounded to serve as the filling agent, a good conductive network can be constructed in a resin matrix, the conductive seepage threshold value is reduced, the mechanical property of the resin matrix is enhanced, and meanwhile the conductivity and the heat conductivity coefficient of the resin matrix can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material processing, and in particular relates to a low dielectric and electromagnetic shielding LCP composite material and a preparation method thereof. Background Art

[0002] With the advent of the 5G era, its high-speed and high-frequency characteristics are driving the rapid development of materials. 5G technology has become increasingly mature, and how to break through the limitations of materials has become a major problem in promoting the advent of the 6G era. At present, due to its low dielectric constant and dielectric loss, the research on LCP materials is becoming more and more extensive. As a material used in signal transmission, the material not only needs to have excellent dielectric properties, but also needs to be able to shield the diffused electromagnetic waves to achieve directional transmission.

[0003] LCP materials cannot perfectly match the above requirements, so how to modify LCP materials is a technical problem that technicians in this field urgently need to solve. Patent Publication No. CN 111548612A discloses a PCT / TLCP resin composition for a 5G antenna vibrator substrate, its preparation method and application. The total weight of the PCT / TLCP resin composition is 100 parts, and includes the following components: 20-65 parts by weight of PCT resin; 5-30 parts by weight of TLCP resin; 20-60 parts by weight of glass fiber; 1-15 parts by weight of a compatible toughening agent; and 0.5-7 parts by weight of other additives. This patent mainly improves the mechanical properties and electroplating properties of the resin composition, but has little effect on dielectric and electromagnetic shielding. Summary of the invention

[0004] In view of the technical problem that the dielectric and electromagnetic shielding properties of LCP materials are poor, the present invention provides a low dielectric, electromagnetic shielding LCP composite material and a preparation method thereof. The prepared LCP composite material not only has a lower dielectric constant, but also has good electromagnetic shielding capability and thermal conductivity.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A low-dielectric and electromagnetic shielding LCP composite material comprises the following raw materials by mass fraction: 44-64.8% LCP resin, 5.2-28% polytetrafluoroethylene resin, 10-15% low-dielectric glass fiber, 10-15% metal-plated low-dielectric glass fiber, 5-10% conductive filler and 3-5% auxiliary agent.

[0007] The LCP resin is thermotropic liquid crystal TLCP.

[0008] The dielectric constant of the low dielectric glass fiber is 3-5.

[0009] The metal-plated low-dielectric glass fiber is obtained by plating metal on the surface of the low-dielectric glass fiber. Preferably, an electroplating process is used when plating the metal layer on the surface of the low-dielectric glass fiber, and the plated metal is silver, zinc and aluminum.

[0010] The conductive filler is one or more of graphite, carbon nanotubes, carbon fibers, graphene and carbon black.

[0011] The auxiliary agent is one or more than two of an antioxidant, a compatibilizer and an antistatic agent.

[0012] The antioxidant comprises a main antioxidant and a secondary antioxidant; the main antioxidant is N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; the secondary antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite; the antistatic agent is polyquaternary ammonium salt; and the compatibilizer is aluminosilicate.

[0013] A method for preparing a low dielectric and electromagnetic shielding LCP composite material comprises the following steps:

[0014] (1) stirring and mixing LCP resin, polytetrafluoroethylene resin, conductive filler and additive to obtain a mixed material;

[0015] (2) uniformly mixing the mixed material, the low dielectric glass fiber and the metal-plated low dielectric glass fiber to obtain a secondary mixed material;

[0016] (3) The secondary mixed material is heated and melted, extruded into granules, and sieved to obtain a low dielectric and electromagnetic shielding LCP composite material.

[0017] The heating and melting temperature is 300-350°C.

[0018] Beneficial effects of the present invention: The present invention uses LCP resin as the matrix resin to compound polytetrafluoroethylene resin, and the obtained resin matrix not only has excellent mechanical properties, weather resistance and solvent resistance, etc., but also has excellent dielectric properties, and the dielectric constant and dielectric loss are very low, the dielectric constant is as low as 2.2, and the dielectric loss is 0.002-0.004. The present invention uses low-dielectric glass fiber, electroplated metal low-dielectric glass fiber and conductive filler as fillers, which can build a good conductive network in the resin matrix, reduce the percolation threshold of conductivity, and enhance the mechanical properties of the resin matrix. At the same time, it can significantly improve the conductivity and thermal conductivity of the resin matrix; the compatibility between LCP resin and polytetrafluoroethylene resin is enhanced by auxiliary agents to make up for the defects and other problems caused by the lack of compatibility. The presence of antioxidants makes the material's anti-aging performance more excellent, better adapting to the problem of accelerated aging speed in different usage scenarios, and antistatic agents make it difficult for composite materials to generate static electricity, resulting in damage to equipment in the application of electronic components. In addition, the conductive filler brings good heat dissipation capability, and the carbon black in the conductive filler can act as a nucleating agent to promote resin crystallization. Based on this, the present application uses conductive fillers, compound low-dielectric glass fibers and electroplated metal low-dielectric glass fibers, and blends them with LCP resin and polytetrafluoroethylene resin. The prepared low-dielectric, electromagnetic shielding LCP composite materials not only have a lower dielectric constant, but also have good electromagnetic shielding capability and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a flow chart for preparing the low dielectric and electromagnetic shielding LCP composite material of this application. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods.

[0024] The present application provides a low-dielectric, electromagnetic shielding LCP composite material, wherein the raw materials of the composite material include, by mass fraction: 44-64.8% of LCP resin, 5.2-28% of polytetrafluoroethylene resin, 10-15% of low-dielectric glass fiber, 10-15% of electroplated metal low-dielectric glass fiber, 5-10% of conductive filler and 3-5% of additives.

[0025] In some possible embodiments, the auxiliary agent includes a primary antioxidant, a high temperature resistant secondary antioxidant, a compatibilizer and an antistatic agent.

[0026] Those skilled in the art can understand that the combination of the primary antioxidant and the high temperature resistant secondary antioxidant can slow down the thermal oxidation rate of the composite material during processing and use, thereby extending the service life of the composite material; the antistatic agent can inhibit the generation of static electricity during the use of the composite material, and the compatibilizer can enhance the compatibility between the LCP resin and the polytetrafluoroethylene resin, thereby improving the stability of the composite material.

[0027] In some possible embodiments, the LCP resin is a thermotropic liquid crystal TLCP.

[0028] LCP materials are divided into three categories, namely lyotropic liquid crystal polymers, thermotropic liquid crystal polymers and pressure-tropic liquid crystal polymers. Lyotropic liquid crystal polymers can only be processed in solution, while pressure-tropic liquid crystal polymers need to be formed under pressure conditions, and thermotropic liquid crystal polymers can be used for extrusion and injection molding. Liquid crystal polymers have a unique two-phase structure of liquid and solid in the molten state, and their solid state is a fibrous crystal. Therefore, thermotropic liquid crystal TLCP materials can achieve the mechanical properties of ordinary engineering materials with tens of percent glass fiber reinforcement without reinforcement; high temperature resistance, heat deformation temperature can reach more than 350℃; with excellent flame retardancy, thermotropic liquid crystal TLCP materials are self-extinguishing to flames, and will not produce toxic smoke when not low; its dielectric properties are also excellent. At room temperature, the dielectric constant is 2.9-3.1, and the dielectric loss is only 0.015; good processing performance, good melt fluidity and thermal stability above the melting point; hot water resistance and steam resistance, can be used in a steam environment. Using thermotropic liquid crystal TLCP resin as the matrix resin can enable the composite material to inherit the above-mentioned excellent properties and have more application fields.

[0029] In some possible embodiments, the polytetrafluoroethylene resin is a suspension polymerized polytetrafluoroethylene resin.

[0030] Those skilled in the art can understand that there are currently two industrial preparation methods for polytetrafluoroethylene resin: suspension polymerization and dispersion polymerization. Compared with polytetrafluoroethylene resin prepared by dispersion polymerization, polytetrafluoroethylene resin prepared by suspension polymerization is more suitable for extrusion granulation. Polytetrafluoroethylene resin has excellent high and low temperature resistance, a glass transition temperature of 327°C, and can be used for a long time in an environment of minus 250°C; it has good lubrication properties and can also act as a lubricant in a blending system; it has excellent aging resistance, solvent resistance and non-flammability; it has excellent dielectric properties, the dielectric constant is usually 2.0-2.1, and the dielectric loss is only 0.00025.

[0031] In some possible embodiments, the low-dielectric glass fiber is a glass fiber with a dielectric constant of 3-5, and the electroplated metal low-dielectric glass fiber is the surface of the above-mentioned low-dielectric glass fiber electroplated with metal. The only difference in preparation method from conventional metal-plated glass fiber is that ordinary glass fiber is replaced with low-dielectric glass fiber, and metals such as aluminum, silver and zinc can be plated by vacuum coating, vapor deposition, hot dipping and electroplating.

[0032] Those skilled in the art can understand that low-dielectric glass fiber is a glass fiber with a dielectric constant of 3-5. While maintaining the original mechanical strength, the dielectric constant and dielectric loss are low. On the one hand, it can enhance the mechanical properties of the resin matrix, and on the other hand, it can avoid causing an increase in the dielectric constant and dielectric loss of the composite material. Electroplating metal on the surface of low-dielectric glass fiber can construct a conductive network, which brings electromagnetic shielding capabilities to the composite material. Electromagnetic shielding theory believes that when electromagnetic waves propagate to the surface of the shielding material, they are usually attenuated by three different mechanisms: absorption loss that is not reflected into the shielding body; reflection loss on the reflecting surface; and multiple reflections inside the shielding body. The reflection loss of electromagnetic waves is closely related to the conductivity of the shielding material. The greater the conductivity of the material, the greater its reflection loss and the stronger the shielding effectiveness of the material.

[0033] In some possible embodiments, the conductive filler is one or more of graphite, carbon nanotubes, carbon fibers, graphene and carbon black.

[0034] Those skilled in the art can understand that an important feature of conductive polymer composite materials is that the conductivity increases nonlinearly with the increase of conductive fillers. When the volume fraction of conductive fillers reaches a certain critical value, the conductivity will increase rapidly, and the variation range can reach more than 10 orders of magnitude. Then the conductivity will slowly decrease with the increase of conductive fillers. This critical value is called the percolation threshold. Electroplated metal glass fibers are in a fibrous shape and have uncertainty in the extrusion process, so the volume fraction at which they reach the percolation threshold is large. After adding conductive fillers, the conductive fillers can connect the electroplated metal glass fibers in series to form a 0-dimensional and 1-dimensional cross-conductive network structure, reducing the volume fraction required for the percolation threshold. And the self-lubricating property of polyetheretherketone resin can also make the conductive fillers better dispersed in the matrix resin, forming a good conductive network and improving the conductivity of the composite material. The essence of heat transfer is the energy transfer phenomenon caused by temperature gradient. From a microscopic perspective, phonons are the quantized energy of lattice vibrations. The temperature gradient causes a concentration difference of phonons. Under the action of the concentration difference, phonons diffuse to form a directional diffusion flow. The directional movement of phonons causes the directional movement of energy, which is heat conduction. However, in the resin matrix, phonons are scattered at the interface by defects and impurities in the amorphous phase, resulting in poor thermal conductivity of the resin matrix. The above-mentioned conductive filler is also a high thermal conductivity material. The thermal conductive network constructed by the filling of the thermal conductive material can effectively enhance the thermal conductivity of the composite material.

[0035] In some possible embodiments, the primary antioxidant includes N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; the high temperature resistant secondary antioxidant includes bis(2,4-dicumylphenyl)pentaerythritol diphosphite; the antistatic agent includes polyquaternary ammonium salt; and the compatibilizer includes aluminosilicate.

[0036] Those skilled in the art can understand that there are active hydrogen atoms in the molecules of the main antioxidant. This H atom is more active than the H atom of the molecular chain, and can combine with the decomposed macromolecular chain free radicals R· or ROO·, thereby destroying the growth of the chain and playing the role of an antioxidant; the auxiliary antioxidant acts on the hydroperoxide produced by the decomposition of organic matter to prevent the generation of free radicals, thereby preventing more free radicals from being continuously generated, so as to maintain the thermal stability of organic matter and extend the service life of organic matter; there are light, heat, and oxygen effects before and after processing. The main antioxidant and the auxiliary antioxidant work synergistically to slow down the thermal oxidation rate of organic matter during processing and use. When the antistatic agent is added to the resin matrix, an antistatic molecular layer can be formed on the surface of the material, and when the molecular layer is damaged, the internal antistatic agent penetrates into the surface of the material, repairs the damaged molecular layer, and plays a role in suppressing static electricity. Aluminosilicate, as a compatibilizer, can reduce the interfacial tension of LCP resin and polytetrafluoroethylene resin, making it more evenly dispersed.

[0037] Based on a general inventive concept, see Figure 1 The second aspect of the present invention provides a method for preparing a low dielectric and electromagnetic shielding LCP composite material. Based on the low dielectric and electromagnetic shielding LCP composite material described in the first aspect, the preparation method comprises:

[0038] S1: mixing LCP resin, polytetrafluoroethylene resin, conductive filler and additives in a high-speed mixer to obtain a mixed material;

[0039] S2: adding the mixed material into a twin-screw extruder from a main feed port, uniformly mixing the low-dielectric glass fiber and the electroplated metal low-dielectric glass fiber, and adding the mixed material and the modified glass fiber into the twin-screw extruder from a side feed port, and uniformly mixing the mixed material and the modified glass fiber in the screw cavity of the twin-screw extruder to obtain a secondary mixed material;

[0040] S3 The secondary mixed material is heated and melted in the screw cavity, extruded into granules, and sieved to obtain a low dielectric and electromagnetic shielding LCP composite material.

[0041] In combination with the second aspect of the present application, before the LCP resin is pre-mixed to obtain the initial mixed material, the process further includes: drying the LCP resin; the drying temperature is 130-150° C., and the drying time is 3-5 hours.

[0042] In conjunction with the second aspect of the present application, the temperature of the heating and melting is 300-350°C.

[0043] Specifically, when preparing low dielectric, electromagnetic shielding LCP composite materials, the LCP resin is first dried, polytetrafluoroethylene resin, conductive filler and additives are added thereto, and the mixture is evenly mixed in a high-speed mixer; the resulting mixture is then added to a twin-screw extruder from a main feed port, and the low dielectric glass fiber and the electroplated metal low dielectric glass fiber are evenly mixed and added to the twin-screw extruder from a feed port on the other side. The raw materials are evenly mixed by heating and melting in the screw cavity, and are made into strips by cooling. After dehydration, they are pelletized and sieved to obtain a low dielectric, electromagnetic shielding LCP composite material with uniform particle size, which is finally packaged and sold.

[0044] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0045] The raw material compositions and test results of the low dielectric and electromagnetic shielding LCP composite materials in Examples 1-6 and Comparative Examples 1-4 are shown in the table:

[0046] Table 1 Raw material composition and experimental data of each embodiment

[0047]

[0048] In the above-mentioned embodiments 1-6 and comparative examples 1-4, the low dielectric glass fiber is TLD-CS-443 of Taishan Fiberglass, with a dielectric constant of 4.3, a short cut length of 3 mm, and a diameter of 10 μm; the ordinary glass fiber is T490 of Taishan Fiberglass, with a dielectric constant of 6.7, a short cut length of 3 mm, and a diameter of 10 μm; the proportion of the main antioxidant and the auxiliary antioxidant in the auxiliary agent is fixed at 0.3wt%, the ratio of the compatibilizer to the antistatic agent is 1:1, the antistatic agent polyquaternary ammonium salt is chlorinated-2-hydroxy-3-(trimethylamino)propyl polyethylene oxide cellulose ether, the compatibilizer is aluminosilicate, the main antioxidant is N, N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, the auxiliary antioxidant is bis(2,4-dicumylphenyl) pentaerythritol diphosphite, and the electroplated metal low dielectric glass fiber is prepared by itself, and the preparation method is as follows:

[0049] Put Taishan Fiberglass's TLD-CS-443 into an anhydrous ethanol pool and soak and stir for 30 minutes to remove oil, then use a mixed solution of 10g / LNH4F and 30mL / LHF to roughen for 15 minutes, wash the roughened glass fiber, pour aminopropyl triethoxysilane into a 50% ethanol solution for hydrolysis, and after the hydrolysis is completed, pour it into a sensitization pool, pour the above glass fiber into the sensitization pool, stir for 2 hours, sensitize, wash after sensitization, activate with 5g / LAgNO3 silver ammonia solution for 20 minutes, wash again after activation, boil glucose and tartaric acid in water for 10 minutes, cool, add a certain amount of ethanol solution, the concentration of the prepared glucose solution is 30g / L, pour the treated glass fiber into the reducing solution, stir for 10 minutes, slowly add 20g / L silver ammonia solution thereto, react for 90 minutes, wash the glass fiber, and dry at 75℃ for 10 hours to obtain silver-plated low-dielectric glass fiber.

[0050] The above-mentioned Examples 1-6 and Comparative Examples 1-4 are all prepared by the following method, the difference being that only the proportion of the components is changed, specifically including:

[0051] S1: drying the LCP resin at 140° C. for 5 h, and mixing the dried LCP resin, polytetrafluoroethylene resin, graphene and additives in a high-speed mixer to obtain a mixed material;

[0052] S2: adding the mixed material into a twin-screw extruder from a main feed port, uniformly mixing the low-dielectric glass fiber and the electroplated metal low-dielectric glass fiber, and adding the mixed material and the modified glass fiber into the twin-screw extruder from a side feed port, and uniformly mixing the mixed material and the modified glass fiber in the screw cavity of the twin-screw extruder to obtain a secondary mixed material;

[0053] S3: The secondary mixed material is heated to 300-350°C in the screw cavity to be melted, extruded into granules, and sieved to obtain a low dielectric and electromagnetic shielding LCP composite material.

[0054] From the above table 1, it can be seen that: by comparing the experimental data of Examples 1-6, the content of the conductive filler graphene increases, and its shielding effectiveness and thermal conductivity first increase and then decrease. This is because after the content of graphene exceeds the percolation threshold and increases rapidly, the content continues to increase and its conductivity will slowly decrease, so the shielding effectiveness and thermal conductivity will first increase and then decrease. Therefore, the low dielectric and electromagnetic shielding LCP composite material of the present application needs to control the mass fraction of the conductive filler to 5-10%.

[0055] Furthermore, compared with comparative examples 1-4, the low-dielectric, electromagnetic shielding LCP composite material prepared in Example 2 of the present invention effectively uses low-dielectric glass fiber, electroplated metal low-dielectric glass fiber and conductive filler, while enhancing the mechanical properties of the composite material through the low-dielectric glass fiber, reducing the impact of the increased dielectric constant caused by the glass fiber; the electroplated metal low-dielectric glass fiber can construct the skeleton of the conductive network of the composite material, and as a glass fiber reinforced material, it can also enhance the mechanical properties of the material; the addition of conductive filler can reduce the percolation threshold of the composite material, achieve a rapid increase in conductivity, and significantly improve the electromagnetic shielding effectiveness of the material.

[0056] LCP resin and polytetrafluoroethylene resin are blended and modified. On the one hand, both have low dielectric constants and dielectric losses, laying the foundation for the dielectric properties of the blended composite material. On the other hand, the two materials have excellent mechanical properties and high temperature resistance and aging resistance. Using them as the matrix resin can effectively cope with applications in complex environments. The addition of conductive fillers such as electroplated metal low-dielectric glass fiber and graphene, through the combination of zero-dimensional and one-dimensional materials, effectively reduces the percolation threshold of the composite material, constructs a conductive network of the composite material, and achieves high electromagnetic shielding and high thermal conductivity of the composite material.

[0057] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0058] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

Claims

1. A low dielectric, electromagnetic shielding LCP composite material, characterized in that: The invention comprises the following raw materials in mass fractions: 44-64.8% of LCP resin, 5.2-28% of polytetrafluoroethylene resin, 10-15% of low dielectric glass fiber, 10-15% of metal-plated low dielectric glass fiber, 5-10% of conductive filler and 3-5% of auxiliary agent.

2. The low dielectric and electromagnetic shielding LCP composite material according to claim 1, characterized in that: The LCP resin is thermotropic liquid crystal TLCP.

3. The low dielectric and electromagnetic shielding LCP composite material according to claim 2, characterized in that: The dielectric constant of the low dielectric glass fiber is 3-5.

4. The low dielectric and electromagnetic shielding LCP composite material according to claim 3, characterized in that: The metal-plated low-dielectric glass fiber is a low-dielectric glass fiber with a metal layer plated on its surface.

5. The low dielectric and electromagnetic shielding LCP composite material according to any one of claims 1 to 4, characterized in that: The conductive filler is one or more of graphite, carbon nanotubes, carbon fibers, graphene and carbon black.

6. The low dielectric and electromagnetic shielding LCP composite material according to claim 5, characterized in that: The auxiliary agent is one or more than two of an antioxidant, a compatibilizer and an antistatic agent.

7. The low dielectric and electromagnetic shielding LCP composite material according to claim 6, characterized in that: The antioxidant comprises a main antioxidant and a secondary antioxidant; the main antioxidant is N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; the secondary antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

8. The low dielectric and electromagnetic shielding LCP composite material according to claim 6, characterized in that: The antistatic agent is polyquaternary ammonium salt; the compatibilizer is aluminum silicate.

9. The method for preparing the low dielectric and electromagnetic shielding LCP composite material according to claim 1, characterized in that: The following steps are involved: (1) stirring and mixing LCP resin, polytetrafluoroethylene resin, conductive filler and additive to obtain a mixed material; (2) uniformly mixing the mixed material, the low dielectric glass fiber and the metal-plated low dielectric glass fiber to obtain a secondary mixed material; (3) The secondary mixed material is heated and melted, extruded into granules, and sieved to obtain a low dielectric and electromagnetic shielding LCP composite material.

10. The method for preparing the low dielectric and electromagnetic shielding LCP composite material according to claim 9, characterized in that: The heating and melting temperature is 300-350°C.

Citation Information

Patent Citations

  • PCT / TLCP resin composition for 5G antenna oscillator base material as well as preparation method and application thereof

    CN111548612A